Failure of Sustainable Waste Management In The Perspective of Community Empowerment in the Garbage Canister Program in Dusun Karang - Amirul Wahid Ridlo Wicaksono Zain; Aziz Muslim (Fakultas Dakwah UIN Kiai Haji Achmad Siddiq Jember, 2024)
This article discusses the failure of sustainable waste management. Given that the problem of waste has always been an actual issue in human life that coexists with the environment. The source of waste problems generally arises because of the paradigm of human awareness in waste management. One of them is what happened to the people of Dusun Karang who manage waste by disposing of it. PMI UIN KHAS Jember students who found this pattern then as facilitators carried out community empowerment in improving environmental functions through the implementation of the waste tube program. Unfortunately, this program ended after the facilitators terminated with the community. This article will take a closer look at how the empowerment process was implemented and why the community chose not to continue the program after the facilitators left, even though the waste problem is an urgent matter to be addressed in a sustainable manner. This research aims to find out how the process of community empowerment in the procurement of a sustainable waste management program and evaluate the weaknesses of the program through a community empowerment perspective. The research method used is a qualitative case study approach through interview, observation, and FGD data search techniques. The resource persons were purposively selected and interviewed regarding the program and the reality that occurred in the community related to the program. The results showed that the facilitators had carried out community empowerment well according to 4 stages, namely problem analysis, planning, implementation, and evaluation and the factors of the community not continuing the program were due to the absence of local heroes, lack of involvement of universities, and little time. Further research can further explore effective solutions to the problems that occur.